Simultaneous Unbinned Differential Cross-Section Measurement of Twenty-Four (Formula presented) Kinematic Observables with the ATLAS Detector - Aad, G.; Åkesson, T.P.A. ; 0000-0003-4141-5408; Astrand, K.S.V.; Doglioni, C.; Ekman, P.A. ; 0000-0002-7032-2799; Hedberg, V.; Herde, H. ; 0000-0001-8926-6734; Konya, B.; Lytken, E. ; 0000-0002-8141-3995; Poettgen, R. ; 0000-0002-3304-0987; Simpson, N.D.; Smirnova, O. ; 0000-0003-2517-531X; et al. (Physical Review Letters, 2024)
(Formula presented) boson events at the Large Hadron Collider can be selected with high purity and are sensitive to a diverse range of QCD phenomena. As a result, these events are often used to probe the nature of the strong force, improve Monte Carlo event generators, and search for deviations from standard model predictions. All previous measurements of (Formula presented) boson production characterize the event properties using a small number of observables and present the results as differential cross sections in predetermined bins. In this analysis, a machine learning method called omnifold is used to produce a simultaneous measurement of twenty-four (Formula presented) observables using (Formula presented) of proton-proton collisions at (Formula presented) collected with the ATLAS detector. Unlike any previous fiducial differential cross-section measurement, this result is presented unbinned as a dataset of particle-level events, allowing for flexible reuse in a variety of contexts and for new observables to be constructed from the twenty-four measured observables. © 2024 CERN, for the ATLAS Collaboration.
Keywords: Binoculars; Colliding beam accelerators; Hadrons; Kinematics; Linear accelerators; Photons; ATLAS detectors; Cross-section measurement; Differential cross-sections; Diverse range; High purity; Large Hadron Collider; Large-hadron colliders; Measurements of; Monte Carlo Event generators; Standard model; Bosons